Linear Noetherian boundary-value problem for a matrix difference equation - Chuiko, S. M.; Kalinichenko , Ya. V.; Boichuk , A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.9 We establish constructive conditions for the solvability and propose a scheme for constructing solutions of a linear Noetherian boundary-value problem for a matrix difference equation.  We suggest an original scheme of regularization of a linear Noetherian boundary-value problem for a linear degenerate system of difference equations.